A DFT study on optical, electronic, and charge transport properties of star‐shaped benzo[1, 2‐b:3, 4‐b′:5, 6‐b″]trithiophene oligomers. (5th December 2019) - Tripathi, Anuj; Kozaderov, Oleg; Shikhaliev, Khidmet; Prabhakar, Chetti
Abstract: We present a study of optical and electronic properties along with reorganization energies in benzo[1, 2‐b:3, 4‐b′:5, 6‐b″]trithiophene (BTT) and its oligomers. The primary objective of this work is to study the effect of the addition of BTT units to the core BTT, on the absorption, electronic, and charge transport properties, using density functional theory (DFT) calculations. The absorption spectra of all molecules were calculated by employing time‐dependent DFT (TDDFT) methodology. The results show that the highest occupied molecular orbital (HOMO), lowest unoccupied molecular orbital (LUMO), HOMO‐LUMO energy gap, ionization potentials (IPs), electron affinities (EAs), and reorganization energies ( λ ) are dramatically affected upon the addition of each BTT unit to the core BTT. Abstract : Enhancement in Charge Transport Properties with the addition of BTT Units.